Micro LED epitaxial structure and preparation method thereof
By adopting a specific epitaxial structure in the Micro LED chip, including a contact layer composed of multi-layer doped materials, the problem of uneven current expansion is solved, the luminous efficiency and stability is improved, the generation of leakage channels is reduced, and the chip is extended service life.
Patent Information
- Application Number
- CN202411785478.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Micro LED chips have uneven current expansion problems when the length and width are relatively large, resulting in excessive local junction temperature of the chip and uneven distribution of luminous luminance, which affects the stability and service life of the chip. At the same time, existing methods are improving the difference in current expansion. Problems often lead to adverse electrical losses such as increased chip leakage.
A Micro LED epitaxial structure is adopted, including a substrate, a buffer layer, a U-GaN layer, an N-GaN layer, a multi-quantum well layer, an electron barrier layer, a P-GaN layer and a contact layer, wherein the contact layer includes a depletion layer and The annealing layer, the depletion layer consists of Mg-doped GaN and Si-doped BGaN, and the annealing layer consists of Ta2O5, Ga2O3 and Mg-doped gradient (AlGa)2O3. Through this structure, the vertical expansion of current is reduced, the horizontal expansion capability of current is improved, and the The generation of contact resistance and leakage channels.
It improves the luminous efficiency and stability of Micro LED chips, reduces the generation of leakage channels, enhances the uniformity and dynamic reliability of current, and extends the service life of the chip.
Smart Images

Figure CN119300569A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor devices, and in particular to a Micro LED epitaxial structure and a preparation method thereof. Background Art
[0002] With the booming development of emerging wearable and portable technologies, micron-sized LED chips (Micro LED) have received great attention and research from scientific research institutions and enterprises due to their application prospects in display, visible light communication, biomedicine and other fields. In addition, Micro LED display has excellent performance such as nanosecond (ns) level high-speed response performance, stable characteristics of inorganic materials, high light efficiency, high reliability, high color purity and contrast, and transparency. The combination of these characteristics is difficult to achieve with liquid crystal display (LCD) and organic LED (OLED).
[0003] Although Micro LED has many excellent properties, most Micro LED electrodes are designed at the two ends of the long side of the chip, which will cause uneven current expansion, resulting in excessive local junction temperature of the chip, and ultimately leading to increased chip voltage and uneven distribution of luminous brightness; and this phenomenon will also cause premature aging of the chip, affecting the stability and service life of the chip.
[0004] In order to solve the problem of poor current expansion when the length and width of LED chips are relatively large, it is usually necessary to do a good job of planar expansion of electron carriers between the nGaN layer and the quantum well light-emitting layer. The so-called current expansion means that the current is evenly distributed throughout the chip; to achieve this goal, the lateral resistance of electron carriers inside the chip should be as small as possible, but the longitudinal resistance should be as large as possible. At present, the general method is to reduce the resistance by increasing the Si doping amount in the GaN layer and to increase the resistance by reducing the Si doping amount, but this approach often leads to increased chip leakage, increased voltage and other undesirable electrical losses. Therefore, while solving the problem of poor current expansion when the length and width of LED chips are relatively large, how to avoid undesirable electrical losses such as increased chip leakage is still a problem that needs to be solved urgently. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to propose a Micro LED epitaxial structure. The Micro LED epitaxial structure of the present invention is used to prepare chips, which can improve the lateral expansion capability of current, reduce contact resistance and reduce the generation of leakage channels, thereby improving the luminous efficiency and stability of the Micro LED chip.
[0006] Another object of the present invention is to provide a method for preparing a Micro LED epitaxial structure, which is used to prepare the above-mentioned Micro LED epitaxial structure.
[0007] To achieve this object, the present invention adopts the following technical solutions: A Micro LED epitaxial structure comprises a substrate, and a buffer layer, a U-GaN layer, an N-GaN layer, a multi-quantum well layer, an electron blocking layer, a P-GaN layer and a contact layer stacked in sequence on the substrate; The contact layer includes a depletion layer and an annealing layer stacked in sequence; The depletion layer includes a Mg-doped GaN layer and a Si-doped BGaN layer stacked in sequence; The annealing layer includes a Ta2O5 layer, a Ga2O3 layer and a Mg-doped graded (AlGa)2O3 layer stacked in sequence.
[0008] Preferably, the thickness of the Mg-doped GaN layer is 3 nm to 10 nm, and the Mg doping concentration in the Mg-doped GaN layer is 5×10 18 atoms / cm 3 ~5×10 19 atoms / cm 3 .
[0009] Preferably, the thickness of the Si-doped BGaN layer is 3 nm to 10 nm, and the Si doping concentration in the Si-doped BGaN layer is 1×10 15 atoms / cm 3 ~5×10 19 atoms / cm 3 .
[0010] Preferably, the thickness of the Mg-doped graded (AlGa)2O3 layer is 1 nm to 5 nm; The Mg doping concentration in the Mg doped graded (AlGa)2O3 layer is 5×10 19 atoms / cm 3 ~5×10 20 atoms / cm 3 , and the Mg doping concentration increases step by step along the growth direction of the epitaxial structure.
[0011] Preferably, the thickness of the Ta2O5 layer is 3nm~10nm, and the thickness of the Ga2O3 layer is 1nm~5nm.
[0012] Preferably, the N-GaN layer is doped with Si, and the Si doping concentration is 1×10 19 atoms / cm 3 ~5×10 20 atoms / cm 3 ; The thickness of the N-GaN layer is 1 μm to 5 μm.
[0013] Preferably, the multi-quantum well layer comprises InGaN quantum well layers and AlGaN quantum barrier layers which are periodically and alternately stacked in sequence, and the number of stacking periods is 5 to 20; The thickness of the InGaN quantum well layer is 2nm~5nm, the growth temperature is 700℃~810℃, the growth pressure is 50torr~300torr, and the proportion of In component is 0.01~0.3; The thickness of the AlGaN quantum barrier layer is 5nm~15nm, the growth temperature is 800℃~900℃, the growth pressure is 50torr~300torr, and the proportion of Al component is 0.01~0.1.
[0014] A method for preparing a Micro LED epitaxial structure, used for preparing the above-mentioned Micro LED epitaxial structure, comprises the following steps: (1) Select substrate; (2) growing a buffer layer on the substrate; (3) Growing a U-GaN layer on the buffer layer; (4) Growing an N-GaN layer on the U-GaN layer; (5) Growing a multi-quantum well layer on the N-GaN layer; (6) growing an electron blocking layer on the multi-quantum well layer; (7) Growing a P-GaN layer on the electron blocking layer; (8) Growing a contact layer on the P-GaN layer.
[0015] Preferably, in step (8), the growth temperature of the contact layer is 600° C. to 1000° C., and the growth pressure is 100 torr to 500 torr.
[0016] Preferably, in step (8), growing a contact layer on the P-GaN layer comprises the following steps: Growing a depletion layer on the P-GaN layer; growing an annealing layer on the depletion layer; The surface of the annealing layer is annealed at a temperature of 600°C to 800°C.
[0017] The implementation of the present invention has the following beneficial effects: The contact layer of the embodiment of the present invention includes a depletion layer and an annealing layer stacked in sequence, the depletion layer includes a Mg-doped GaN layer and a Si-doped BGaN layer, and the annealing layer includes a Ta2O5 layer, a Ga2O3 layer and a Mg-doped gradient (AlGa)2O3 layer. The depletion layer in the contact layer can reduce the vertical expansion of the current during the recombination process, indirectly improve the lateral expansion capability of the current, and thus improve the uniformity of the light emission. The Ga2O3 layer can ensure the crystal quality of the Mg-doped gradient (AlGa)2O3 layer, the Mg-doped gradient (AlGa)2O3 layer can make the work function of the contact layer close to the electrode, reduce the contact resistance of the contact layer, and thus improve the luminous efficiency of the Micro LED, and the Mg-doped gradient (AlGa)2O3 layer has a higher bandgap width, between 5eV and 5.3eV, and at a higher bandgap width, it can effectively prevent the mobility of electrons, thereby reducing the generation of leakage channels. Therefore, the annealing layer has higher dynamic reliability, lower current collapse, and can form a charge inversion structure, which improves reliability and thus improves photoelectric performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a schematic structural diagram of a Micro LED epitaxial structure in Embodiment 1 of the present invention; Figure 2 yes Figure 1 Schematic diagram of the structure of the contact layer in the Micro LED epitaxial structure shown; Among them, substrate 1, buffer layer 2, U-GaN layer 3, N-GaN layer 4, multi-quantum well layer 5, electron blocking layer 6, P-GaN layer 7, contact layer 8, depletion layer 81, annealing layer 82, Mg-doped GaN layer 811, Si-doped BGaN layer 812, Ta2O5 layer 821, Ga2O3 layer 822 and Mg-doped gradient (AlGa)2O3 layer 823. DETAILED DESCRIPTION
[0019] To make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0020] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. Raw materials used without specifying the manufacturer are all conventional products that can be obtained through commercial purchase.
[0021] like Figure 1 and Figure 2As shown, a Micro LED epitaxial structure includes a substrate 1, and a buffer layer 2, a U-GaN layer 3, an N-GaN layer 4, a multi-quantum well layer 5, an electron blocking layer 6, a P-GaN layer 7 and a contact layer 8 stacked in sequence on the substrate; The contact layer 8 includes a depletion layer 81 and an annealing layer 82 stacked in sequence, and the depletion layer 81 is connected to the P-GaN layer 7; The depletion layer 81 includes a Mg-doped GaN layer 811 and a Si-doped BGaN layer 812 stacked in sequence; The annealing layer 82 includes a Ta2O5 layer 821, a Ga2O3 layer 822 and a Mg-doped graded (AlGa)2O3 layer 823 which are stacked in sequence.
[0022] It is worth noting that, in one embodiment, the contact layer 8 includes a depletion layer 81 and an annealing layer 82 stacked in sequence, the depletion layer 81 includes a Mg-doped GaN layer 811 and a Si-doped BGaN layer 812, and the annealing layer 82 includes a Ta2O5 layer 821, a Ga2O3 layer 822, and a Mg-doped graded (AlGa)2O3 layer 823. The depletion layer 81 in the contact layer can reduce the vertical expansion of the current during the recombination process, indirectly improve the lateral expansion capability of the current, and thus improve the uniformity of the light emission. The Ga2O3 layer 822 can ensure the crystal quality of the Mg-doped gradient (AlGa)2O3 layer 823. The Mg-doped gradient (AlGa)2O3 layer 823 can make the work function of the contact layer close to that of the electrode, reduce the contact resistance of the contact layer, and thus improve the luminous efficiency of the Micro LED. The Mg-doped gradient (AlGa)2O3 layer 823 has a higher bandgap width, between 5eV and 5.3eV. At a higher bandgap width, it can effectively prevent the migration of electrons, reduce the electron mobility, and thus reduce the generation of leakage channels. Therefore, the annealed layer 82 has higher dynamic reliability, lower current collapse, can form a charge inversion structure, improve the reliability of the epitaxial structure, and thus improve the photoelectric performance.
[0023] Specifically, the bandgap width of the Mg-doped gradient (AlGa)2O3 layer 823 is between 5eV and 5.3eV, and the proportion of Al component is 0.01~0.1. In the Mg-doped gradient (AlGa)2O3 layer 823, the required bandgap width can be controlled by the Al component. As the Al component increases, the bandgap width will increase accordingly.
[0024] In one embodiment, the substrate may be a sapphire substrate, an AlN substrate, a Si substrate, a SiC substrate, or the like.
[0025] Specifically, the substrate is a sapphire substrate, which is currently the most commonly used substrate material. The sapphire substrate has the advantages of mature preparation technology, low price, easy cleaning and processing, and good stability at high temperatures.
[0026] It is worth noting that the depletion layer includes a Mg-doped GaN layer 811 and a Si-doped BGaN layer 812 stacked in sequence, the thickness of the Mg-doped GaN layer 811 is 3nm~10nm, and the Mg doping concentration in the Mg-doped GaN layer 811 is 5×10 18 atoms / cm 3 ~5×10 19 atoms / cm 3 ; The thickness of the Si-doped BGaN layer 812 is 3nm~10nm, and the Si doping concentration in the Si-doped BGaN layer 812 is 1×10 15 atoms / cm 3 ~5×10 19 atoms / cm 3 , so that the depletion layer in the contact layer can reduce the vertical expansion of the current during the recombination process, indirectly improve the lateral expansion capability of the current, and thus improve the uniformity of light emission.
[0027] The Mg doping concentration in the Mg-doped GaN layer 811 is 5×10 18 atoms / cm 3 ~5×10 19 atoms / cm 3 , exemplarily 5×10 18 atoms / cm 3 , 6×10 18 atoms / cm 3 ,7×10 18 atoms / cm 3 , 8×10 18 atoms / cm 3 ,9×10 18 atoms / cm 3 , 1×10 19 atoms / cm 3 , 2×10 19 atoms / cm 3 , 3×10 19 atoms / cm 3 , 4×10 19 atoms / cm 3 , 5×10 19 atoms / cm 3 , but not limited to this.
[0028] The Si doping concentration in the Si-doped BGaN layer 812 is 1×10 15 atoms / cm 3 ~5×10 19 atoms / cm 3 , exemplarily 1×10 15 atoms / cm 3 , 2×10 15 atoms / cm 3 , 5×10 15 atoms / cm 3 ,9×10 15 atoms / cm 3 , 1×10 16 atoms / cm 3 , 3×10 16 atoms / cm 3 , 5×10 16 atoms / cm 3 , 8×10 16 atoms / cm 3 , 1×10 17 atoms / cm 3 , 3×10 17 atoms / cm 3 , 5×10 17 atoms / cm 3 , 8×10 17 atoms / cm 3 , 1×10 18 atoms / cm 3 , 3×10 18 atoms / cm 3 , 5×10 18 atoms / cm 3 , 8×10 18 atoms / cm 3 , 1×10 19 atoms / cm 3 , 3×10 19 atoms / cm 3 , 5×10 19 atoms / cm 3 , but not limited to this.
[0029] Further explanation, the thickness of the Mg-doped gradient (AlGa)2O3 layer 823 is 1 nm to 5 nm; the Mg doping concentration in the Mg-doped gradient (AlGa)2O3 layer 823 is 5×10 19 atoms / cm 3 ~5×10 20atoms / cm 3 , and the Mg doping concentration increases step by step along the growth direction of the epitaxial structure, so that the Mg-doped gradient (AlGa)2O3 layer 823 has a higher bandgap width between 5eV and 5.3eV, which can effectively prevent the migration of electrons and thus reduce the generation of leakage channels.
[0030] To further illustrate, the thickness of the Ta2O5 layer 821 is 3nm~10nm, and the thickness of the Ga2O3 layer 822 is 1nm~5nm.
[0031] In one embodiment, the annealing layer includes a Ta2O5 layer 821, a Ga2O3 layer 822, and a Mg-doped gradient (AlGa)2O3 layer 823 stacked in sequence, wherein the thickness of the Ta2O5 layer 821 is 3nm~10nm, the thickness of the Ga2O3 layer 822 is 1nm~5nm, the thickness of the Mg-doped gradient (AlGa)2O3 layer 823 is 1nm~5nm, and the Mg doping concentration in the Mg-doped gradient (AlGa)2O3 layer 823 is 5×10 19 atoms / cm 3 ~5×10 20 atoms / cm 3 , and the Mg doping concentration increases step by step along the direction of epitaxial structure growth, so that the annealing layer can increase the current expansion capability and evenly distribute the current flow direction to prevent current concentration from forming current breakdown, so that the annealing layer has higher dynamic reliability, lower current collapse, and can form a charge reversal structure, which improves reliability and thus improves photoelectric performance. In addition, the Ga2O3 layer 822 can ensure the crystal quality of the Mg-doped gradient (AlGa)2O3 layer, and the Mg-doped gradient (AlGa)2O3 layer 823 can make the work function of the contact layer close to that of the electrode, reduce its contact resistance, and improve the luminous efficiency of the MicroLED.
[0032] In one embodiment, the thickness of the Mg-doped GaN layer 811, the Si-doped BGaN layer 812, and the Ta2O5 layer 821 are all 3nm to 10nm, exemplarily 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, but not limited thereto. The thickness of the Ga2O3 layer 822 and the Mg-doped graded (AlGa)2O3 layer 823 are all 1nm to 5nm, exemplarily 1nm, 2nm, 3nm, 4nm, 5nm, but not limited thereto.
[0033] In one embodiment, the buffer layer 2 is an AlN buffer layer, which is deposited in PVD with a thickness of 45nm~60nm. The AlN buffer layer provides a nucleation center with the same orientation as the substrate, releases the stress generated by the lattice mismatch between AlGaN and the substrate and the thermal stress generated by the mismatch of thermal expansion coefficients, provides a flat nucleation surface for further growth, reduces the contact angle of its nucleation growth, and enables the island-like grown GaN grains to be connected into a surface within a smaller thickness, transforming into two-dimensional epitaxial growth, thereby improving the crystal quality of the subsequently deposited GaN layer, reducing the dislocation density, and improving the radiation recombination efficiency of the multi-quantum well layer.
[0034] More preferably, the thickness of the buffer layer 2 is 50 nm to 60 nm.
[0035] In one embodiment, a U-GaN layer 3 is deposited on the AlN buffer layer, the thickness of the U-GaN layer 3 is 1 μm to 3 μm, the growth temperature is 1100° C. to 1150° C., and the growth pressure is 100 torr to 500 torr. The growth temperature of the U-GaN layer 3 is high and the pressure is low, so that the crystal quality of the prepared U-GaN layer 3 is better.
[0036] More preferably, the thickness of the U-GaN layer 3 is 2 μm-3 μm, the growth temperature is 1100° C.-1120° C., and the growth pressure is 250 torr-400 torr.
[0037] In an optional embodiment of the present invention, the growth temperature of the U-GaN layer 3 is 1100° C., the growth pressure is 300 torr, and the growth thickness is 2 μm.
[0038] In one embodiment, the N-GaN layer 4 is doped with Si, and the Si doping concentration is 1×10 19 atoms / cm 3 ~5×10 20 atoms / cm 3 The thickness of the N-GaN layer 4 is preferably 1 μm to 5 μm, the growth temperature of the N-GaN layer 4 is preferably 1000°C to 1300°C, and the growth pressure is preferably 50 torr to 300 torr. First, the N-GaN layer 4 provides sufficient electrons and holes for the LED to recombine. Secondly, the resistivity of the n-type doped N-GaN layer 4 is higher than that of the transparent electrode on the P-type GaN layer. Therefore, sufficient Si doping can effectively reduce the resistivity of the N-GaN layer 4. Finally, the sufficient thickness of the N-GaN layer 4 can effectively release stress and improve the luminous efficiency of the light-emitting diode.
[0039] More preferably, the growth temperature of the N-GaN layer 4 is 1200° C. to 1300° C., the growth pressure is 100 torr to 300 torr, the growth thickness is 2 μm to 3 μm, and the Si doping concentration is 2.5×10 19 atoms / cm 3 ~5×10 19 atoms / cm 3 .
[0040] In one embodiment, the multi-quantum well layer 5 includes InGaN quantum well layers and AlGaN quantum barrier layers that are periodically and alternately stacked in sequence, and the number of stacking periods is 5 to 20; the thickness of the InGaN quantum well layer is 2 nm to 5 nm, the growth temperature is 700 ° C to 810 ° C, the growth pressure is 50 torr to 300 torr, and the proportion of In component is 0.01 to 0.3; the thickness of the AlGaN quantum barrier layer is 5 nm to 15 nm, the growth temperature is 800 ° C to 900 ° C, the growth pressure is 50 torr to 300 torr, and the proportion of Al component is 0.01 to 0.1. The multi-quantum well layer is the area where electrons and holes recombine. Reasonable structural design can significantly increase the overlap of electron and hole wave functions, thereby improving the luminous efficiency of LED devices.
[0041] Specifically, in an optional embodiment of the present invention, the multi-quantum well layer includes alternately stacked InGaN quantum well layers and AlGaN quantum barrier layers, with a stacking period of 10, wherein the growth temperature of the InGaN quantum well layer is 765°C, the thickness is 3.5nm, the pressure is 200torr, and the In component is 0.23; the growth temperature of the AlGaN quantum barrier layer is 855°C, the thickness is 9.8nm, the growth pressure is 200torr, and the Al component is 0.05.
[0042] Further explanation, the electron blocking layer 6 is an AlInGaN layer, the thickness of the electron blocking layer 6 is 10nm~40nm, the growth temperature is 900℃~1000℃, the growth pressure is 100torr~300torr, wherein the Al component accounts for 0.01~0.1, and the In component accounts for 0.01~0.2, which can effectively limit electron overflow, reduce the blocking of holes, improve the injection efficiency of holes into quantum wells, reduce carrier Auger recombination, and improve the luminous efficiency of light-emitting diodes.
[0043] More preferably, the thickness of the electron blocking layer 6 is 10 nm to 20 nm, the proportion of Al component is 0.03 to 0.06, the proportion of In component is 0.01 to 0.05, the growth temperature is 950° C. to 980° C., and the growth pressure is 150 torr to 250 torr.
[0044] Specifically, in an optional embodiment of the present invention, the electron blocking layer is an AlInGaN layer with a thickness of 15 nm, wherein the Al component accounts for 0.05, the In component accounts for 0.01, the growth temperature is 965° C., and the growth pressure is 200 torr.
[0045] Further explanation, the P-GaN layer 7 is doped with Mg, and the Mg doping concentration is 1×10 19 atoms / cm 3 ~1×10 21 atoms / cm 3 Too high Mg doping concentration will damage the crystal quality, while a low doping concentration will affect the hole concentration; the thickness of the P-GaN layer 7 is 10nm~50nm, the growth temperature is 900℃~1050℃, and the growth pressure is 100torr~600torr.
[0046] More preferably, the Mg doping concentration in the P-GaN layer 7 is 1×10 20 atoms / cm 3 ~5×10 20 atoms / cm 3 The thickness of the P-GaN layer 7 is 10 nm to 20 nm, the growth temperature is 950° C. to 1000° C., and the growth pressure is 150 torr to 250 torr.
[0047] Specifically, in one embodiment of the present invention, the growth temperature of the P-GaN layer 7 is 985° C., the thickness is 15 nm, the growth pressure is 200 torr, and the Mg doping concentration is 2×10 20 atoms / cm 3 .
[0048] A method for preparing a Micro LED epitaxial structure, used for preparing the above-mentioned Micro LED epitaxial structure, comprises the following steps: (1) Select substrate 1; (2) growing a buffer layer 2 on the substrate 1; (3) growing a U-GaN layer 3 on the buffer layer 2; (4) growing an N-GaN layer 4 on the U-GaN layer 3; (5) growing a multi-quantum well layer 5 on the N-GaN layer 4; (6) growing an electron blocking layer 6 on the multi-quantum well layer 5; (7) growing a P-GaN layer 7 on the electron blocking layer 6; (8) A contact layer 8 is grown on the P-GaN layer 7 .
[0049] The technical solution adopts MOCVD (Metal-organic Chemical Vapor Deposition, MOCVD for short) equipment, one of high-purity H2 (hydrogen), high-purity N2 (nitrogen), and a mixed gas of high-purity H2 and high-purity N2 as a carrier gas, high-purity NH3 as an N source, trimethylgallium (TMGa) and triethylgallium (TEGa) as gallium sources, trimethylaluminum (TMAl) as an aluminum source, silane (SiH4) as an N-type dopant, and bis(cyclopentadienyl)magnesium (CP2Mg) as a P-type dopant for epitaxial growth.
[0050] In one embodiment, in step (8), the growth temperature of the contact layer 8 is 600°C to 1000°C, exemplarily 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, but not limited thereto. The growth pressure of the contact layer 8 is 100 torr to 500 torr, exemplarily 100 torr, 120 torr, 150 torr, 180 torr, 200 torr, 250 torr, 300 torr, 400 torr, 500 torr, but not limited thereto.
[0051] To further illustrate, in step (8), growing the contact layer 8 on the P-GaN layer 7 includes the following steps: Growing a depletion layer 81 on the P-GaN layer 7; Growing an annealing layer 82 on the depletion layer 81; The surface of the annealing layer 82 is annealed at a temperature of 600° C. to 800° C. Exemplary annealing temperatures are 600° C., 650° C., 700° C., 750° C., and 800° C., but are not limited thereto.
[0052] The technical scheme of the present invention is further described below through examples and comparative examples.
[0053] Example 1 The Micro LED epitaxial structure of this embodiment includes a substrate 1, and a buffer layer 2, a U-GaN layer 3, an N-GaN layer 4, a multi-quantum well layer 5, an electron blocking layer 6, a P-GaN layer 7 and a contact layer 8 stacked in sequence on the substrate; the contact layer 8 includes a depletion layer 81 and an annealing layer 82 stacked in sequence, the depletion layer 81 includes a Mg-doped GaN layer 811 and a Si-doped BGaN layer 812 stacked in sequence, and the annealing layer 82 includes a Ta2O5 layer 821, a Ga2O3 layer 822 and a Mg-doped gradient (AlGa)2O3 layer 823 stacked in sequence.
[0054] Among them, the thickness of the Mg-doped GaN layer 811 is 5 nm, the thickness of the Si-doped BGaN layer 812 is 6 nm, the thickness of the Ta2O5 layer 821 is 5 nm, the thickness of the Ga2O3 layer 822 is 3 nm, and the thickness of the Mg-doped graded (AlGa)2O3 layer 823 is 3 nm; The Mg doping concentration in the Mg-doped GaN layer 811 is 1×10 19 atoms / cm 3 ; The Si doping concentration in the Si-doped BGaN layer 812 is 5×10 17 atoms / cm 3 ; The Mg doping concentration in the Mg-doped graded (AlGa)2O3 layer 823 is 5×10 19 atoms / cm 3 ~9.5×10 19 atoms / cm 3 , and the Mg doping concentration increases from 5×10 19 atoms / cm 3 Gradually increases to 9.5×10 19 atoms / cm 3 .
[0055] The buffer layer 2 of this embodiment is an AlN buffer layer with a thickness of 50 nm; the U-GaN layer 3 is grown with a thickness of 2 μm; the N-GaN layer 4 is grown with a thickness of 3 μm, and the Si doping concentration is 2.5×10 19 atoms / cm 3 ; The multi-quantum well layer 5 is a periodically alternately stacked InGaN quantum well layer and AlGaN quantum barrier layer, and the number of stacking periods is 10; wherein the thickness of the InGaN quantum well layer is 3.5 nm, and the In component is 0.23; the thickness of the AlGaN quantum barrier layer is 9.8 nm, and the Al component is 0.05; The electron blocking layer 6 is AlInGaN with a thickness of 15 nm, wherein the Al component concentration is 0.05 and the In component concentration is 0.01; the thickness of the P-GaN layer 7 is 15 nm, and the Mg doping concentration is 2×10 20 atoms / cm 3 .
[0056] The method for preparing the Micro LED epitaxial structure of this embodiment includes the following steps: (1) Selecting substrate 1, which is a sapphire substrate; (2) growing a buffer layer 2 on the substrate; (3) growing a U-GaN layer on the buffer layer 2 at a growth temperature of 1100°C and a growth pressure of 300 torr; (4) growing an N-GaN layer 4 on the U-GaN layer at a growth temperature of 1200°C and a growth pressure of 100 torr; (5) growing a multi-quantum well layer 5 on the N-GaN layer 4, wherein the growth temperature of the InGaN quantum well layer is 765°C and the growth pressure is 200 torr; the growth temperature of the AlGaN quantum barrier layer is 855°C and the growth pressure is 200 torr; (6) growing an electron blocking layer 6 on the multi-quantum well layer 5 at a growth temperature of 965° C. and a growth pressure of 200 torr; (7) growing a P-GaN layer 7 on the electron blocking layer 6 at a growth temperature of 985° C. and a growth pressure of 200 torr; (8) A contact layer 8 is grown on the P-GaN layer 7, wherein a depletion layer is first grown on the P-GaN layer 7, and then an annealing layer is grown on the depletion layer. The growth temperatures of the depletion layer and the annealing layer are both 850°C and the growth pressures are both 150 torr. The surface of the annealing layer is then annealed at a temperature of 700°C.
[0057] Example 2 The structural composition and preparation method of the Micro LED epitaxial structure of this embodiment are basically the same as those of Embodiment 1, except that the thickness of the Mg-doped gradient (AlGa)2O3 layer 823 of this embodiment is 5 nm, and the Mg doping concentration in the Mg-doped gradient (AlGa)2O3 layer 823 is 8×10 19 atoms / cm 3 ~5×10 20 atoms / cm 3 , and the Mg doping concentration increases from 8×10 19 atoms / cm 3 Gradually increases to 5×10 20 atoms / cm 3 .
[0058] Example 3 The structural composition and preparation method of the Micro LED epitaxial structure of this embodiment are basically the same as those of Embodiment 1, except that the thickness of the Mg-doped GaN layer 811 of this embodiment is 8 nm, and the Mg doping concentration in the Mg-doped GaN layer 811 is 4×10 19 atoms / cm 3 ; The thickness of the Si-doped BGaN layer 812 is 5 nm, and the Si doping concentration in the Si-doped BGaN layer 812 is 8×10 18atoms / cm 3 .
[0059] Comparative Example 1 The structural composition and preparation method of the Micro LED epitaxial structure of this comparative example are basically the same as those of Example 1, except that the contact layer of this comparative example is a P-type InGaN layer.
[0060] Comparative Example 2 The structural composition and preparation method of the Micro LED epitaxial structure of this comparative example are basically the same as those of Example 1, except that the Mg doping concentration in the Mg-doped gradient (AlGa)2O3 layer of the Micro LED epitaxial structure of this comparative example is 5×10 19 atoms / cm 3 , and the Mg doping concentration is constant.
[0061] Comparative Example 3 The structural composition and preparation method of the Micro LED epitaxial structure of this comparative example are basically the same as those of Example 1, except that the contact layer of this comparative example is only provided with an annealing layer but no depletion layer.
[0062] Comparative Example 4 The structural composition and preparation method of the Micro LED epitaxial structure of this comparative example are basically the same as those of Example 1, except that the contact layer of this comparative example is only provided with a depletion layer but no annealing layer.
[0063] Performance Test: The Micro LED epitaxial structures obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were prepared into 3mil×5mil chips using the same chip process conditions, and their performance was tested on the same Micro LED spot tester: (1) Photoelectric performance: The test was conducted at a working current of 2 mA, and the light efficiency improvement rate of Examples 1 to 3 and Comparative Examples 2 to 4 compared with Comparative Example 1 was calculated.
[0064] (2) Antistatic ability: The antistatic performance of the chip was tested using an electrostatic meter under the HBM (human body discharge model) model to test the pass rate of the chip that can withstand reverse 4000V static electricity, and the pass rate improvement rate (i.e., ESD improvement rate) of Example 1 to Example 3 and Comparative Example 2 to Comparative Example 4 compared with Comparative Example 1 was calculated.
[0065] Specifically, the performance test results are shown in Table 1 below.
[0066] Table 1 Performance test results
[0067] It can be seen from the above experimental data that the use of the contact layers of Examples 1 to 3 can improve the lateral current expansion capability of the Micro LED epitaxial structure, reduce contact resistance and reduce the generation of leakage channels, thereby effectively improving the luminous efficiency, antistatic ability and reliability of the Micro LED chip.
[0068] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A Micro LED epitaxial structure, characterized in that: It comprises a substrate, and a buffer layer, a U-GaN layer, an N-GaN layer, a multi-quantum well layer, an electron blocking layer, a P-GaN layer and a contact layer stacked in sequence on the substrate; The contact layer includes a depletion layer and an annealing layer stacked in sequence; The depletion layer includes a Mg-doped GaN layer and a Si-doped BGaN layer stacked in sequence; The annealing layer includes a Ta2O5 layer, a Ga2O3 layer and a Mg-doped graded (AlGa)2O3 layer stacked in sequence.
2. The Micro LED epitaxial structure according to claim 1, characterized in that: The thickness of the Mg-doped GaN layer is 3nm-10nm, and the Mg doping concentration in the Mg-doped GaN layer is 5×10 18 atoms / cm 3 ~5×10 19 atoms / cm 3 .
3. The Micro LED epitaxial structure according to claim 1, wherein: The thickness of the Si-doped BGaN layer is 3nm-10nm, and the Si doping concentration in the Si-doped BGaN layer is 1×10 15 atoms / cm 3 ~5×10 19 atoms / cm 3 .
4. The Micro LED epitaxial structure according to claim 1, wherein: The thickness of the Mg-doped graded (AlGa)2O3 layer is 1nm~5nm; The Mg doping concentration in the Mg doped graded (AlGa)2O3 layer is 5×10 19 atoms / cm 3 ~5×10 20 atoms / cm 3 , and the Mg doping concentration increases step by step along the growth direction of the epitaxial structure.
5. The Micro LED epitaxial structure according to claim 1, wherein: The thickness of the Ta2O5 layer is 3nm~10nm, and the thickness of the Ga2O3 layer is 1nm~5nm.
6. The Micro LED epitaxial structure according to claim 1, wherein: The N-GaN layer is doped with Si, and the Si doping concentration is 1×10 19 atoms / cm 3 ~5×10 20 atoms / cm 3 ; The thickness of the N-GaN layer is 1 μm to 5 μm.
7. The Micro LED epitaxial structure according to claim 1, wherein: The multi-quantum well layer comprises InGaN quantum well layers and AlGaN quantum barrier layers which are periodically and alternately stacked in sequence, and the number of stacking periods is 5 to 20; The thickness of the InGaN quantum well layer is 2nm~5nm, the growth temperature is 700℃~810℃, the growth pressure is 50torr~300torr, and the proportion of In component is 0.01~0.3; The thickness of the AlGaN quantum barrier layer is 5nm~15nm, the growth temperature is 800℃~900℃, the growth pressure is 50torr~300torr, and the proportion of Al component is 0.01~0.
1.
8. A method for preparing a Micro LED epitaxial structure, characterized in that: The method for preparing the Micro LED epitaxial structure according to any one of claims 1 to 7 comprises the following steps: (1) Select substrate; (2) growing a buffer layer on the substrate; (3) Growing a U-GaN layer on the buffer layer; (4) Growing an N-GaN layer on the U-GaN layer; (5) Growing a multi-quantum well layer on the N-GaN layer; (6) growing an electron blocking layer on the multi-quantum well layer; (7) Growing a P-GaN layer on the electron blocking layer; (8) Growing a contact layer on the P-GaN layer.
9. The method for preparing a Micro LED epitaxial structure according to claim 8, characterized in that: In step (8), the growth temperature of the contact layer is 600° C. to 1000° C., and the growth pressure is 100 torr to 500 torr.
10. The method for preparing a Micro LED epitaxial structure according to claim 8, characterized in that: In step (8), growing a contact layer on the P-GaN layer comprises the following steps: Growing a depletion layer on the P-GaN layer; growing an annealing layer on the depletion layer; The surface of the annealing layer is annealed at a temperature of 600°C to 800°C.
Citation Information
Patent Citations
Light-emitting diode epitaxial wafer capable of improving luminous efficiency and preparation method of light-emitting diode epitaxial wafer
CN113410353A
Light-emitting diode epitaxial wafer, preparation method thereof and light-emitting diode
CN117253950A
Ultraviolet light-emitting diode epitaxial wafer, preparation method thereof and light-emitting diode
CN117650211A
Light-emitting diode epitaxial wafer, preparation method thereof and light-emitting diode
CN117855355A
Low-voltage Micro-LED epitaxial wafer, preparation method thereof and Micro-LED
CN119069598A